Aircraft observation of cloud microphysical characteristics of pre-stratiform-cloud precipitation in Jiangxi Province. Issue 5 (3rd September 2017) - Fu, Yuan; Lei, Heng-Chi
Abstract: Based on Droplet Measurement Technologies data of a pre-stratiform-cloud precipitation event in Ganzhou, Jiangxi Province, on 11 November 2015, and combined with radar data, this paper comprehensively analyzes the macro- and microphysical characteristics of cloud in the upper trough. The results show that: (1) Detection takes place in the early stage of precipitation and the cloud has multiple layers. The cloud type is stratiform (Sc) and the height of the cloud base is 1009 m, 1009–1700 m is the low Sc layer, 1700–3000 m is the no-cloud level, and 3000 to the maximum height detected is another Sc layer. (2) The Sc is inhomogeneous in the horizontal and vertical directions. The particle number concentration and the effective diameter below the 0 °C layer is significantly higher than that above the 0 °C layer, which is in accordance with the 'seeder–feeder' mechanism. Above the 0 °C layer is seeder cloud, where needle, column ice crystals and water droplets coexist, and sublimation and coalescence are the main processes. The morphology of ice crystals changes from needle to column, plate, and polymer as height decreases. Below the 0 °C warm layer is a supply cloud, and the particles develop in the supply cloud with abundant liquid water content. Ice melting and coalescence dominate the warm layer, which makes the effective diameter significantly increase. Down to 4150 m, the ice melts completely into raindrops.